(untitled) (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: This study aimed to determine acaricide resistance in Rhipicephalus decoloratus ticks collected from grazing cattle between November 2018 and May 2019 in Elundini, Senqu, and Walter Sisulu Local Municipalities in the northeastern region of the Eastern Cape Province. Materials and Methods: A sample of 20–30 adult engorged female R. decoloratus ticks were collected from at least 10 randomly selected cattle (highly tick-infested) at each dip tank and placed into the labelled plastic collection bottles containing absorbent paper and with a perforated lid at a constant room temperature of ±28°C and >70% relative humidity until resistance testing commenced. The Shaw larval immersion test method was used to determine R. decoloratus larvae resistance to various acaricide concentration levels [amidines, organophosphate (OP), and synthetic pyrethroids (SPs)]. Results: This study found that most ticks were susceptible to exposure to different acaricide field concentrations of amidines (49% at 250 ppm), OPs (33% and 47% at 300 ppm and 500 ppm, respectively), and SPs (44% and 23% at 150 ppm and 300 ppm, respectively). The resistance testing resultsshowed no resistance to amidines at any localities and no resistance to OP in the Senqu region. However, resistance development of the larvae to amines, OPs, and SPs was extensively observed in Senqu (18%, 6%, and 7%), Elundini (15%, 15%, and 17%), and Walter Sisulu (13%, 19%, and 9%) regions, respectively. Conclusions: The larvae’sresistance is a cause for worry. Hence, the continuous monitoring of tick resistance to commonly used acaricides will help mitigate widespread acaricidal resistance and sustain livestock productivity. J. Adv. Vet. Anim. Res., 9(1): 33–41, March 2022 http://doi.org/10.5455/javar.2022.i566